Ethics Relevance of Interpersonal Communication in Ihya Ulun Al-Din with Islamic Communication - Muttaqien Muttaqien; Mohd Hatta; Zainal Arifin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
The purpose of this research were to analyze and relate what was conveyed by Al-Ghazali about communication and interpersonal through his work which was abandoned by the author 900 years ago with the phenomenon of conventional communication developed by communication experts in the current era with the formulation of the problem namely; First, what is the ethics of Interpersonal communication in the Ulum Al-Din Ihya book by Imam Al-Ghazali: Second, What is the relevance of the ethics of interpersonal communication in IhyaUlum Al-Din by Imam Al-Ghazali with Islamic communication ethics in the Qur'an, - Imam Al-Ghazali's work qualitatively regarding the ethics of interpersonal communication. Primary data sources, namely the main data source of the author is literature by Imam al-Ghazali, especially in Sufism which focuses on the book IhyaUlum Al-Din. In terms of data collection, the author took a library survey technique and literature study, a library survey that is collecting data in the form of a number of literature. The collected data will be analyzed using the principle of content analysis. Research findings include; 1). Ethics of Interpersonal Communication according to Imam Al-Ghazali in the book IhyaUlum Al-din, consists of ethics messages on interpersonal communication with fellow human beings which includes good oral communication ethics, mutual help and forgiveness of others, have a generous nature. The relevance of Imam Al-Ghazali's communication ethics with Islamic religious communication contained in the Koran, in that context, there are six da'wah communications according to the Qur'an or also called Islamic communication principles.